Evaluation of Changes in VO2max of FTME UPN Students in the First Two Semesters of Study: A Multistage Fitness Test Approach - Prijoto, Prijoto; Kurniati, Rizki; Yulianto, Wahyu Wibowo Eko; Indriharta, Lilik; Nugraheningsih, Ginanjar (Physical Education, Health and Recreation Study Program, Universitas Insan Budi Utomo, Indonesia, 2025)
This study aims to evaluate changes in students' cardiorespiratory capacity at the Faculty of Mineral and Energy Engineering (FTME) UPN